2019
DOI: 10.2196/10995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electronic and Paper-Pen Data Capturing Tools for Data Quality in a Public Health Survey in a Health and Demographic Surveillance Site, Ethiopia: Randomized Controlled Crossover Health Care Information Technology Evaluation

Abstract: Background Periodic demographic health surveillance and surveys are the main sources of health information in developing countries. Conducting a survey requires extensive use of paper-pen and manual work and lengthy processes to generate the required information. Despite the rise of popularity in using electronic data collection systems to alleviate the problems, sufficient evidence is not available to support the use of electronic data capture (EDC) tools in interviewer-administered data collecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 30 publications
5
30
0
4
Order By: Relevance
“…Similarly, a study was conducted to evaluate the electronic and paper-pen data collection tools for data quality in a public health survey in a health and demographic site, Ethiopia. 23The study found that better data quality and e ciency-fewer errors, instant data submission and easy handling, however, implementing agencies need to consider availability of power source, decent internet connection, technical support and security for the mobile device users for full implementation and integration into surveillance system (23,24). Also a similar study in China on comparing digital data collection and paper/pen data collection for infant feeding practices corroborates the same results of better data quality and fewer errors.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similarly, a study was conducted to evaluate the electronic and paper-pen data collection tools for data quality in a public health survey in a health and demographic site, Ethiopia. 23The study found that better data quality and e ciency-fewer errors, instant data submission and easy handling, however, implementing agencies need to consider availability of power source, decent internet connection, technical support and security for the mobile device users for full implementation and integration into surveillance system (23,24). Also a similar study in China on comparing digital data collection and paper/pen data collection for infant feeding practices corroborates the same results of better data quality and fewer errors.…”
Section: Discussionmentioning
confidence: 67%
“…A study conducted in Sudan, in 2016, compared the smartphone and paper-based data collection systems on the Burden of Obstructive Lung Disease (BOLD) in Gezira State, a rural state in Sudan. The study concluded that digital data collection provided timely quality data with fewer errors and inconsistencies compared to paper-based data collection (23).…”
Section: Discussionmentioning
confidence: 98%
“…Bangladesh site is also implementing a full electronic data capturing system (EDC). EDC has some proven benefits in limiting data collection errors, data quality checks, efficiency, real-time data collection progress monitoring, and data sharing in comparison to paper-pen data capturing [ 6 ]. Like other GN sites, Bangladesh MNHR site will also continuously generate critical maternal and newborn health outcome estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate data collection and management is an essential component of the MNHR which enrolls approximately 60,000 participants per year across 8 global sites (6). Bangladesh is the most recent country to join the GN and has implemented a full electronic MNH registry system, from married women surveillance to pregnancy enrollment and follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Given the total number of discrepancies detected and the little time and resources needed to perform this QC step, we would highly recommend to perform double data entry when digitizing raw data collected on paper. It has been suggested in a number of studies that electronic data collection reduces the number of errors [12,13], is more time-and cost-efficient [12][13][14][15] and yields data that is immediately available for analysis [12,16,17]. This could indeed simplify and standardize the reporting and sharing of study results, and hence be of particular interest to country program managers and other stakeholders.…”
Section: Double Data Entry Reduces the Number Of Erroneous Data Entrimentioning
confidence: 99%